(untitled) (Fiep Bulletin - online, 2013)
This paper presents a theoretical interpretation of the soccer player’s job based on the notion of immaterial work. Although the soccer player’s expertise involves quantifiable and measurable aspects related to material work, such as salary, contract, working hours that consist of practice, games and so on; there are subjective and immeasurable elements that are not quantifiable. The latter may be analyzed from two analytical dimensions, which are: a) that of the subject who works; and, b) that of the product of his work. Therefore, in the soccer player’s activity, the subject’s sports talent is a major issue to be considered, since it then becomes the main product of his work and of the collective intelligence: the sports event.